Clear Resin Casting of Arthropods of Medical Importance for Use in Educational and Outreach Activities. Issue 2 (3rd April 2018) - Bejcek, Justin R; Curtis-Robles, Rachel; Riley, Michael; Brundage, Adrienne; Hamer, Sarah A; Hamer, Gabriel L
Abstract: Arthropod-related morbidity and mortality represent a major threat to human and animal health. An important component of reducing vector-borne diseases and injuries is training the next generation of medical entomologists and educating the public in proper identification of arthropods of medical importance. One challenge of student training and public outreach is achieving a safe mounting technique that allows observation of morphological characteristics, while minimizing damage to specimens that are often difficult to replace. Although resin-embedded specimens are available from commercial retailers, there is a need for a published protocol that allows entomologists to economically create high-quality resin-embedded arthropods for use in teaching and outreach activities. We developed a detailed protocol using readily obtained equipment and supplies for creating resin-embedded arthropods of many species for use in teaching and outreach activities.